(untitled) (Research, Society and Development, 2023)
With the aging of the population, there has been an increase in the prevalence of diseases that lead to the appearance of wounds, such as diabetes, heart disease, cancer and hypertension. And that in the long term they can become injuries that require surgical intervention for the resolution of the patient’s well-being. The objective of this study is to understand the performance of plastic surgeries, not only in the aesthetic scope, but also in the treatment of complex injuries. An integrative literature review was performed. The bibliographic survey was carried out from 2018 to 2023, with consultation in the databases of the Virtual Health Library (VHL): MEDLINE, LILACS, BINACIS and IBECS, using the descriptors: “wounds and injuries”, “plastic surgery” and “treatment”, in conjunction with the Boolean operator and. The use of descriptors resulted in 195 studies. Their selection was carried out by applying the filters followed by reading the titles, abstracts and full texts, meeting the established inclusion and exclusion criteria. Results proved that many complex wounds must be treated with surgical procedures, since only clinical measures make the process more time consuming. In addition, debridement, skin grafts and flaps should be indicated early. In this perspective, the plastic surgeon is essential in the treatment and healing. Thus, there are countless techniques used for the treatment of complex wounds within plastic surgery, ensuring more efficient healing and going far beyond aesthetics.